INTEGRASI LATIHAN VESTIBULAR-POSTURAL (V-POST) DALAM MENINGKATKAN KONTROL MOTORIK: STUDI KASUS PADA ANAK DENGAN GANGGUAN SENSORI DAN PERILAKU DI KLINIK X SURABAYA: Indonesia - Khabib Abdullah; Nura Maulida Isna; Sarah As Syifa (JPK : Jurnal Penelitian Kesehatan, 2026)
Sensory Processing Disorder (SPD) adversely affects motor control, weakens postural muscles, and causes physical instability in children. Cases at Clinic X Surabaya indicate that this physical issue is frequently accompanied by behavioral challenges such as sensory seeking, hyperactivity, and poor focus, as the child feels unsafe against gravity (gravitational insecurity), which triggers a stress response (fight-or-flight). To overcome the limitations of conventional therapy that only strengthens muscles in isolation, this single-subject research with an A-B design evaluates the level 2 hybrid protocol "V-POST" (Vestibular-Postural Exercise Integration). The research subject was Master A (male, 5 years old) at Clinic X Surabaya, who was trained twice a week for 8 weeks (total of 16 sessions, 60 minutes each). This therapy combines vestibular stimulation using a gym ball and a swing with functional exercises such as dynamic squats, balance discs, and a balance beam. Evaluations using SATCo, PBS, and Behavior Observation Sheets showed improved capabilities in the subject. Postural stability (SATCo) increased by 2 levels from Mid-Thoracic to Lower-Lumbar, the PBS balance score rose by 50% (from 32 to 48 points) with single-leg stance capability jumping from 0 to 5–7 seconds, and focus duration increased by 300% (from 3 to 12 minutes) followed by a decrease in hyperactive behavior. In conclusion, this case study on a child with sensory and behavioral disorders proves that the V-POST protocol is highly effective in enhancing the child's motor control.